2012
DOI: 10.4028/www.scientific.net/amm.249-250.400
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Based Gas Path Fault Diagnosis for Turbo-Shaft Engine

Abstract: In order to diagnose the starting fail fault of the certain turbo shaft engine which often occurs in daily use, the experiments for the micro pump and the fuel filter were carried out by the method of contrast test. Through the comparison and analysis, the differences between domestic components and French-made ones were found. The results showed that: The outlet pressure of domestic micro pump is smaller under the engine's working condition; the flux of it is significantly lower under high outlet pressure; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Besides, they need different types of faulty data to obtain classifiers for achieving fault isolation as in refs. [17,[27][28][29][30][31][32]. On the other hand, the methods which do not require faulty data are only concerned with the detection, like in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they need different types of faulty data to obtain classifiers for achieving fault isolation as in refs. [17,[27][28][29][30][31][32]. On the other hand, the methods which do not require faulty data are only concerned with the detection, like in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides machinery fault diagnosis, SVM-DS method were also used in character recognition research according to Guo and Zhang [11]. Another evolution of BPA selection is to use Least squares SVM (LSSVM) which Lu et al have compared the LSSVM with Back Propagation Neural Network (BPNN) and Radial Based Function Neural Network (RBF-NN) to compare the accuracy of LSSVM and D-S [12]. It was reported that the advantages of SVM technique as compare to other machine learning techniques such as can be used for small samples, sample's non-linearity, over fitting, local minimum value and also has excellent generalization ability.…”
Section: Svm In D-s Applicationmentioning
confidence: 99%